1988
DOI: 10.1001/archderm.1988.01670020062019
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Subepidermal Blistering in Split-Thickness Skin Graft Sites

Abstract: We describe a child who began developing subepidermal blisters in the recipient sites of split-thickness skin grafts; this process has continued for almost a year and continues to spare nongrafted skin. Routine histologic and immunofluorescence mapping studies demonstrated this disorder to be a relatively noninflammatory one characterized by sub-lamina densa blister formation. Results of direct immunofluorescence were negative. By electron microscopy, anchoring fibrils were sparse in number and in some areas a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…BSSs are commercially available, easy to apply, and eliminate the need for donor‐site harvesting. Although skin substitutes have been used to facilitate healing of chronic wounds in EB patients, 5,7,24–26 their role in postsurgical defects in this population needs to be further investigated. In an open‐label, uncontrolled study of 15 EB patients, Falabella and colleagues reported faster and less painful healing without adverse effects in 69 wounds treated with the Apligraf (Organogenesis Inc, Canton, Mass) 26 .…”
Section: Discussionmentioning
confidence: 99%
“…BSSs are commercially available, easy to apply, and eliminate the need for donor‐site harvesting. Although skin substitutes have been used to facilitate healing of chronic wounds in EB patients, 5,7,24–26 their role in postsurgical defects in this population needs to be further investigated. In an open‐label, uncontrolled study of 15 EB patients, Falabella and colleagues reported faster and less painful healing without adverse effects in 69 wounds treated with the Apligraf (Organogenesis Inc, Canton, Mass) 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Bullae have been noted to occur at the recipient sites of split-thickness skin grafts.I2 The etiology of these bullae is not known although they may share ultrastructural and antigenic similarities with epidermolysis bullosa acquisita. 13 We have not had any patients develop this complication.…”
Section: Complicationsmentioning
confidence: 90%
“…44 Thus, the appearance of blisters and associated ultrastructural abnormalities following thermal burns, split-thickness skin grafting, and cultured autografting is a well-recognized phenomenon that is not peculiar to cultured autografting alone. The recipient sites were all resected down to fascia before grafting to ensure that the cultured epithelium was not contributed to by the epithelial cells from hair follicles or skin appendages.…”
Section: Histology Of Culture-grafted Epidermismentioning
confidence: 99%